It's Not Where You're From, It's Where You're At. (July 2015) - Watts, Mark; Luebkeman, Chris
<x xml:space="preserve">Abstract</x> Climate change and sustainability expert Mark Watts imagines what it might be like to look back from the year 2050. What might the view be from his position as Executive Director of the C40 Cities Climate Leadership Group? What crucial political moves and actions might be required from global megacities if they are to address climate change and make the ultimate shift to a low‐carbon world?